Radiative relaxation of relativistic electron beam in helical undulator - Ognivenko, V.V. (Вопросы атомной науки и техники, 2006)
A process of radiative relaxation of the monoenergetic relativistic electron beam, moving through a static spatially periodic helical magnetic field is investigated theoretically. Interaction of electron with random incoherent electromagnetic field of spontaneous radiation is shown to lead to spread in the electron-momentum. The conditions necessary for self-amplified spontaneous emission process realization in the short-wavelength region are derived.